HISTORY OF THE DEVELOPMENT OF HADITH (COMPARATIVE OF SHI'AH AND SUNNI) - Khabibul Khoiri; Kholid Akhmad Muzakki (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2021)
The phenomenon of the development of Hadith in the Shia and Sunni groups, we find that the Shia Hadith itself is actually not as complicated and complex as that in the Sunni tradition. This is because the Shia system has been writing hadith for a long time since the beginning of Islam. In addition, there are also differences in views between the two groups regarding the hadith itself. The source of hadith according to the Shia is not only the prophet Muhammad, but every ma'shum imam can also issue a hadith that is used as evidence. With the focal point of religious belief in the priests of the age (the Imamate system), it is very natural that thesystem of transmitting hadith among Shiites has begun to be used during the days of Ali bin Abu Talib. Therefore, it can be concluded that the Shia from the early years had a concern for isnad